Pelatihan Pengolahan Limbah Gorengan Untuk Pembuatan Biodiesel Dan Pakan Ternak Di Kelurahan Curug, Bogor - Fathaddin, Muhammad Taufiq; Ischak, Mohammad; Maulani, Mustamina; Damayanti, Sisca; Irvan, Rayhan; Mahanggi, Muhammad F.Z.; Arkaan, Muhammad Dzaki; Buana, Firdha Meidya (Jurnal Migasian, 2024)
Fried food waste can have negative impacts on environmental and health problems. On the other hand, fried food waste can be processed into biodiesel and animal feed. So that the utilization of fried food waste can increase the supply of fuel and animal feed which continues to increase along with the increasing population in Indonesia. Cooking oil is a renewable material because it comes from palm oil, coconut, corn, soybeans and others. So that the manufacture of biodiesel and animal feed can be preserved and developed in the future. Based on these problems, community service activities (PkM) in RT 3 and RT 5 located in RW 13, Curug Village, Bogor. This PkM activity was attended by 20 participants and was carried out in five stages. The first and second stages were in the form of counseling containing the delivery of material on making biodiesel and animal feed. In the third and fourth stages, training was given on making biodiesel and animal feed. While in the fifth stage, monitoring and evaluation were carried out. The indicators of the success of this activity were evaluated based on the pre-test and post-test values ​​carried out for both biodiesel making activities and animal feed making activities. Based on the evaluation of the comparison of pre-test and post-test assessments carried out by participants, it shows an increase in understanding of biodiesel production from an average value of 38 to 75 or an average increase of 99%. While the increase in understanding of animal feed production from an average value of 21 to 69 or an average increase of 224%. This activity received high attention from the local community. In addition to increasing understanding and expertise regarding biodiesel production, participants also increased their awareness to maintain environmental sustainability and maintain health.